KETERAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN MATEMATIKA: LITERATURE REVIEW - Zainal, Nur Fitriani; Arismunandar, Arismunandar; Suardi, Suardi (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Thinking is one of the abilities that humans have to distinguish them from other creatures through cognitive processing of information. One type of thinking ability that is an important skill in the 21st century is critical thinking skills. This research is a literature review that describes the definition of critical thinking, indicators of critical thinking and mathematics learning that supports the development of critical thinking. Critical thinking skills are very important to develop in mathematics learning because it can optimize students' mathematical problem solving abilities at various levels of problems and other mathematical abilities through reasoning, identifying and analyzing problems; identifying various possible solutions, reviewing assessing each possible solution and deciding on solutions with evidentiary arguments; reflecting through the delivery of solutions based on critical thinking reviews that have been carried out so that it has implications for mathematics learning outcomes and even as capital in facing life's challenges.